Rethinking Nuclear Receptors as Potential Therapeutic Targets for Retinal Diseases. (December 2016) - Choudhary, Mayur; Malek, Goldis
Collectively, retinal diseases, including age-related macular degeneration, retinitis pigmentosa, and diabetic retinopathy, result in severe vision impairment worldwide. The absence and/or limited availability of successful drug therapies for these blinding disorders necessitates further understanding their pathobiology and identifying new targetable signaling pathways. Nuclear receptors are transcription regulators of many key aspects of human physiology, as well as pathophysiology, with reported roles in development, aging, and disease. Some of the pathways regulated by nuclear receptors include, but are not limited to, angiogenesis, inflammation, and lipid metabolic dysregulation, mechanisms also important in the initiation and development of several retinal diseases. Herein, we present an overview of the biology of three diseases affecting the posterior eye, summarize a growing body of evidence that suggests direct or indirect involvement of nuclear receptors in disease progression, and discuss the therapeutic potential of targeting nuclear receptors for treatment.